2021
DOI: 10.3389/fphar.2021.732760
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Hospital Readmission of Heart Failure Patients

Abstract: Background: Heart failure (HF) is a significant cause of mortality, morbidity and impaired quality of life and is the leading cause of readmissions and hospitalization. This study aims to identify the factors contributing to readmission in patients with HF.Methods: A prospective-observational single-centre study was conducted in Sheikh Shakhbout Medical City, Abu Dhabi, United Arab Emirates. A total of 146 patients with HF are included in the study. Patient’s demographics, patient medical characteristics, lab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…This study found that those patients who had lower hemoglobin levels at discharge during index admission increased the risk of unplanned readmission to the hospital compared to a normal hemoglobin level. This study is consistent with the study conducted by the European Society of Cardiology (41), the United Arab Emirates (42), India(43), and the meta-analysis of 26 studies in patients with the comorbidity of heart failure and anemia(44).…”
Section: Discussionsupporting
confidence: 91%
“…This study found that those patients who had lower hemoglobin levels at discharge during index admission increased the risk of unplanned readmission to the hospital compared to a normal hemoglobin level. This study is consistent with the study conducted by the European Society of Cardiology (41), the United Arab Emirates (42), India(43), and the meta-analysis of 26 studies in patients with the comorbidity of heart failure and anemia(44).…”
Section: Discussionsupporting
confidence: 91%
“…NYHA classification is the oldest classification used for HF, which is based on the evaluation of symptom severity and the ability to sustain effort. It has a prognostic value [44], with an increasing hospitalisation and death risk, according to the rising class number [1,42,45]. Class I includes patients with no symptoms exacerbated by ordinary physical activity.…”
Section: The Confusing New York Heart Association Classificationmentioning
confidence: 99%
“…Previous studies have identified hemoglobin level, BP at admission, patient’s compliance to treatment, age, NYHA functional class, diabetes, hypothyroidism, and hypertension as independent factors for HF readmission within 6 months. [32], [33] The reason for lack of statistically significant association between readmissions and patients’ factors or HF treatment factors in our study could be low statistical power to detect these associations. A bigger sample size would potentially have more events and significant associations.…”
Section: Discussionmentioning
confidence: 94%